STEM Learning Method (Science, Technology, Engineering, and Mathematics) in Enhancing Student Competency: A Case Study at SDN Sempur. Plered. Purwakarta - Nana Herdiana Abdul Rahman; Suharyanto Soro; Andi Saleh; Lilih Nurmilah; Dian Rini Handayani (Global Education Journal, 2025)
This research aims to find and analyze the implementation of STEM (Science, Technology, Engineering, and Mathematics) learning methods in improving student competence. The researcher uses a qualitative research paradigm with a case study approach. A sample of 22 (total sampling) educators used a structured questionnaire instrument. The results of the study showed that (1) The level of initial understanding and commitment of educators to STEM methods reached 99%; (2) Practically 21 respondents have applied this method and (99%) believe that the STEM approach is very effective in improving students' critical thinking, creativity, analytical, and complex problem-solving skills; (3) The phenomenon of polarizing experience 11 (50%) of respondents still faces technical obstacles in its implementation; (4)Phase C (Grades 5-6) was identified as the most optimal level for STEM reinforcement with a percentage of 54.5%. This study concludes that STEM learning methods can improve student competence.